The potential impact of post-COVID symptoms in the healthcare sector. (20th August 2021) - Tempany, M; Leonard, A; Prior, A R; Boran, G; Reilly, P; Murray, C; O'Brien, M; Maguire, G; Ennis, D; Rakovac, A; Reid, A
Abstract: Background: The phenomenon of post-COVID syndrome (PCS) is evolving from an abstract array of non-specific symptoms to an identifiable clinical entity of variable severity. Its frequency and persistence have implications for service delivery and workforce planning. Aims: This study was aimed to assess the prevalence of symptoms consistent with PCS and the subjective degree of recovery in a cohort of healthcare workers, focusing on those who have returned to work. Methods: A study population of 1176 was surveyed when attending for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibody testing. Two sub-groups were identified: those with known (i.e. diagnosed on PCR testing) and assumed (i.e. antibody evidence of previous infection) SARs-CoV-2 infection, at least 12 weeks prior to the study. Each group was asked about their subjective degree of recovery and the nature of their persistent symptoms. Results were analysed via excel and SPSS. Results: In total, 144 employees showed PCR evidence of previous infection, with 139 of these being infected at least 12 weeks prior to the study. Of these 139, only 19% ( n = 26) reported feeling 100% recovered, and 71% reported persistent symptoms. Of those with assumed SARS-CoV-2 infection ( n = 78), 32 (41%) were truly asymptomatic since the commencement of the pandemic, while 46 (59%) described symptoms suggestive of possible infection at least 12 weeks prior to the study. Of this latter group, 23% ( n = 18) also reported residual symptoms. Conclusions: PCS is prevalent among this group, including those not previously diagnosed with COVID-19. Its' frequency and duration present challenges to employers with regards to the management of work availability and performance.